Litigating in the shadow of death : defense attorneys in capital cases - White, Welsh S., 1940- (University of Michigan Press, 2009)
"Anyone who cares about capital punishment should read this compelling, lucid account of the obstacles defense attorneys face and the strategies they adopt."--John Parry, University of Pittsburgh School of Law "With its compelling narratives of cases, strategies, and ethical dilemmas, Litigating in the Shadow of Death is difficult to put down. ... This pathbreaking book encapsulates the experience of the most respected capital defenders in America and shows how they save even the worst of the worst from execution. It also shows how sleeping and otherwise incompetent lawyers bring death sentences to their clients. Litigating in the Shadow of Death explores the lawyers' tasks at every stage of the criminal process--investigation, client interviewing, conferring with victims' families, plea bargaining, trial, appeal, and post-conviction proceedings."--Albert W. Alschuler, Julius Kreeger Professor of Law and Criminology, University of Chicago "A unique and profoundly important contribution to the literature on the death penalty. White allows the leading capital defense attorneys to speak in their own voices. His work reveals a new source of arbitrariness in the death system--whether the penalty is imposed turns more on who is your lawyer than on how evil was your deed or your character. Litigating in the Shadow of Death offers concrete guidelines for better lawyering, protection of the innocent, and understanding the artistry of the best capital attorneys. This is vivid, gripping stuff."--Andrew Taslitz, Professor of Law, Howard University "A most illuminating book by a splendid writer and an eminent critic of the capital punishment system."--Yale Kamisar, Professor of Law, University of San Diego "Welsh White has written another excellent book on the death penalty--this one on how defense attorneys in capital cases successfully prevent the state from executing their clients. Based on original research, Litigating in the Shadow of Death is informative and insightful. This is a book that all serious students of American capital punishment must read." --Richard Leo, University of California, Irvine Welsh S. White was Bessie McKee Walthour Endowed Chair and Professor of Law at the University of Pittsburgh.